To reflect the function \( f(x) = x + 1 \) about the origin, we need to transform the function into \(-f(-x)\).
Step 1: Find \(-f(-x)\)
-
Substitute \(-x\) into the function: \[ f(-x) = -x + 1 \]
-
Now apply the negative sign: \[ -f(-x) = -(-x + 1) = x - 1 \]
So, the reflected function is \( g(x) = x - 1 \).
Step 2: Find the new position of the point (-4, 9)
To find where the point \((-4, 9)\) reflects to under the new function \(g(x)\):
-
First, determine the x-coordinate of the reflection: \[ x = 4 \quad \text{(since reflection over the origin flips the sign of both coordinates)} \]
-
Now, calculate \(g(4)\): \[ g(4) = 4 - 1 = 3 \]
Conclusion
The reflected point of \((-4, 9)\) in the function \(g(x)\) is: \[ (4, 3) \]
Thus, the position of the point \((-4, 9)\) in the reflected function is \((4, 3)\).